2004
DOI: 10.1097/00130404-200405000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Margins Predict Biochemical Outcomes After Prostate Brachytherapy

Abstract: V(100), D(90), and TMs all appear to have a bearing on biochemical freedom from relapse after prostate brachytherapy. Efforts to better identify and test geographic dosimetric parameters are theoretically appealing, and supported by the clinical data summarized here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…There is general agreement that, ideally, treatment margins should be in the range of 3 to 5 mm (5,17,18). Our margin study cohort represents the largest unselected series with systematically determined treatment margins around an MR-defined prostate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is general agreement that, ideally, treatment margins should be in the range of 3 to 5 mm (5,17,18). Our margin study cohort represents the largest unselected series with systematically determined treatment margins around an MR-defined prostate.…”
Section: Discussionmentioning
confidence: 99%
“…Implant quality parameters concentrate on the dose received by the prostate, quantified by the D90 (isodose enclosing 90% of the prostate volume) and V100 (the percentage of the prostate volume enclosed by the prescription isodose), and do not take into account the dose to the CTV or the periprostatic tissue at risk for microscopic disease (4,5). Although the issue of what constitutes an adequate periprostatic treatment margin for dose-escalated external beam radiotherapy has been extensively investigated (6)(7)(8)(9), the margin obtained with iodine-125 brachytherapy is unknown.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obtaining satisfactory values of D90 (the dose that covers 90% of the prostate volume outlined on the postimplantation computed tomography [CT] images) and V100 (fractional volume of the prostate that receives 100% of the prescription dose) with adequate margins to the prostate is important for achieving high rates of biochemical control, and it has been demonstrated that higher V150 values (volume receiving N150% of the prescribed dose) are typically required to maintain satisfactory coverage when 103 Pd is used, despite the fact that the American Association of Physicists in Medicine recommends a V150 below 50%. [10][11][12][13][14][15][16] Because a high V150 may lead to increased urinary morbidity, we reviewed our outcomes with either isotope in an unselected cohort of patients treated consecutively at our institution.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] There are also reports linking the size of treatment margins with biochemical outcome. 5 Accordingly, these 3 parameters are becoming the basis for QA assessment.…”
mentioning
confidence: 99%